2012
DOI: 10.1111/j.1365-3156.2012.03041.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adults and children diagnosed with tuberculosis in Lilongwe, Malawi: findings from an integrated HIV/TB clinic

Abstract: Objectives To describe initial registration characteristics of adult and pediatric TB patients at a large, public, integrated TB and HIV clinic in Lilongwe, Malawi, between January 2008 – December 2010. Methods Routine data on TB patient category and TB type, stratified by HIV and ART status, were used to explore differences in proportions among TB-only, TB/HIV co-infected patients not on ART, and TB/HIV co-infected patients on ART using Chi-square tests.. Trends over time illustrate strengths and weaknesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This study has established that EPTB is more common in males (3.0%) than females (1.8%). This is similar to studies conducted in African countries and elsewhere which found that men are more affected than women [ 7 – 9 , 15 , 24 , 25 ]. The possible explanation to this similarity finding could be due to resemblance in health-seeking behaviour in our set up whereby females seek medical care more frequently and earlier than males, hence posing more chance for male to be a highly affected group of people [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study has established that EPTB is more common in males (3.0%) than females (1.8%). This is similar to studies conducted in African countries and elsewhere which found that men are more affected than women [ 7 – 9 , 15 , 24 , 25 ]. The possible explanation to this similarity finding could be due to resemblance in health-seeking behaviour in our set up whereby females seek medical care more frequently and earlier than males, hence posing more chance for male to be a highly affected group of people [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“… Notes: The number of studies and the sample size contributed by 12 countries from SSA that had included studies were as follows: ten studies with 2,837 people with HIV/AIDS were from Ethiopia, 18 27 four each were from Nigeria (2,042) 28 31 and South Africa (13,929), 32 35 and three were from Cameroon (2,246). 11 , 36 , 37 Two each were from Uganda (245) 38 , 39 and Zambia (471), 40 , 41 one each was from Tanzania (175), 42 Benin (521), 43 Burkina Faso (112), 44 Malawi (5,561), 45 Kenya (846), 46 and Gabon (205) 47 ( Table 1 ). …”
Section: Figurementioning
confidence: 99%
“…4 Some high-burden African settings have reported a pediatric TB-HIV co-infection burden of 43.4% and above. 5,6 In Malawi, high TB incidence (191 per 100 000 population in 2011) and HIV prevalence (11% in 2009), along with limited TB diagnostic tools and challenges in early infant diagnosis of HIV, make management of co-infected children a challenge, resulting in poor outcomes. 7–10 …”
mentioning
confidence: 99%